Precision control of microstructure variation and tensile properties in dissimilar friction stir lap welding joints using an adjustable tool - Amlan Kar; Yoshiaki Morisada; Abhishek Sharma; Hidetoshi Fujii (Scientific Reports)
Abstract Friction-assisted plastic deformation at the joint interface is essential for achieving the desired joint properties in dissimilar friction stir lap welding (FSLW) of aluminum alloy (Al) with steel (Fe). This plastic deformation can be precisely controlled by using an adjustable tool, where shoulder and probe rotation speeds are independently controlled. This study explores the effect of microstructure evolution and probe rotation speed on the weld’s interface morphology and tensile properties of FSLW joints between an aluminum alloy and steel using an adjustable tool. Microstructure evolution is influenced by inherent material properties and process-induced stress inhomogeneity. Grain refinement in Fe is more gradual compared to Al, which exhibits a homogenous microstructure. Lower probe rotation speeds lead to more significant grain refinement in Al, while increasing probe rotation speeds promote the formation of intermetallic compounds. An intercalated structure with varying fractions and morphology is observed across the joint interface in all welds. The controlled evolution of microstructure and the differences in intercalated structure formation at the weld interface are attributed to variations in shear strength. This study demonstrates the ability of an adjustable tool to tailor the microstructure and tensile properties of FSLW joints, providing a promising approach for enhancing joint performance in dissimilar metal joining applications.